Permeability and Enterotoxic Factors of Nonagglutinable Vibrios Vibrio alcaligenes and Vibrio parahaemolyticus - Bhattacharya, S. (1971)
Enterotoxic factor (EF) was present and could be developed in nonagglutinable vibrios, but not the permeability factor (PF). Presence of PF without EF in Vibrio parahaemolyticus is significant. Both EF and PF were absent in V. alcaligenes.